Understanding regulation in complex environments: a route to enhance photosynthetic light-reactions in microalgae photobioreactors - Perin, Giorgio; Morosinotto, Tomas (Frontiers in Photobiology, 2023)
Microalgae are recognized as a sustainable source of biomass to produce a wide range of bioproducts. To maximize the positive environmental impact and achieve economic competitiveness of microalgae-based products, it is however still essential to improve the biomass productivity during large-scale cultivation. Microalgae large-scale cultures are generally limited by light availability and thus the efficiency in conversion of radiation energy into biomass is a major factor impacting productivity. Natural light is a highly variable environmental parameter, and it constantly changes following seasons, time of day, and weather conditions. The artificial environment of large-scale microalgae cultures generates a further layer of complexity added to these natural light dynamics. In fact, because of biomass density and cell self-shading, light is unevenly distributed in the mass culture. Moreover, because of mixing, cells move between different parts of the volume, generating abrupt fluctuations in light exposure. Although microalgae evolved various regulatory mechanisms to cope with dynamic light conditions, these are not adapted to respond to the complex mixture of natural and artificial fluctuations commonly encountered in large-scale cultures, often causing reduction in photosynthetic efficiency. In the past years, genetic approaches to improve the light reactions of photosynthesis have been explored to optimise the composition and regulation of the photosynthetic machinery to large-scale cultivation. These approaches have shown promising results at the laboratory scale but have yet to be fully proven at the industrial scale. This can be explained by the fact that the complexity of the cultivation environment on microalgae photosynthesis and its impact on productivity is underestimated. This work aims for a systematic discussion on the complex role played by the growth environment in determining microalgae photosynthetic performances upon cultivation at industrial scale, with the objective of maximizing the impact of genetic modifications and ultimately fully realize the potential of microalgae for biomass productivity.